2011
DOI: 10.1007/s12011-011-9110-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Copper on Morphology, Weight, and Chromosomal Aberrations in the Spiny Lobster, Panulirus homarus (Linnaeus, 1758)

Abstract: Spiny lobster Panulirus homarus which had been exposed to cupric ion at 9.55 and 19.1 μg/l for 28 days was examined for sub-lethal effects including morphology, wet weight, and induced genotoxic effect on the chromosome. Following cupric exposure, the color of lobster P. homarus changed from yellowish-brown to greenish black in the hepatopancreas, changed from normal creamy white to yellowish white in the muscle, and changed to greenish black in the gill. A significant change in the percentage of wet weight of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…In the shore crab, Carcinus maenus, the recovery processes involved the cytological damage of the gill epithelium (Stentiford and Feist, 2005). A variety of acclamatory effects have also been documented in fish and lobster chronically exposed to sublethal levels of copper (Grosell et al, 1998;Maharajan et al, 2011Maharajan et al, , 2012aMaharajan et al, ,b, 2013Paruruckumani et al, 2015a,b).…”
Section: Introductionmentioning
confidence: 99%
“…In the shore crab, Carcinus maenus, the recovery processes involved the cytological damage of the gill epithelium (Stentiford and Feist, 2005). A variety of acclamatory effects have also been documented in fish and lobster chronically exposed to sublethal levels of copper (Grosell et al, 1998;Maharajan et al, 2011Maharajan et al, , 2012aMaharajan et al, ,b, 2013Paruruckumani et al, 2015a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Baden et al (1994) also reported similar changes in the distribution of glycogen in the tissues of Norway lobster, Nephrops norvegicus exposed to copper. Maharajan et al (2010aMaharajan et al ( , 2010bMaharajan et al ( , 2011Maharajan et al ( , 2012 observed copper accumulation, electrical conductivity, chromosome aberration and histopathological changes in various tissues of spiny lobster, P.hoamrus homarus when exposed to sub-lethal doses of copper.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the simultaneous decrease in oxygen consumption and metabolic data, leading to an energy imbalance that may have influenced net growth efficiency. Maharajan et al [110] detected cytogenic effects of Cu in lobster (Panulirus homarus) exposed to different concentrations of the cupric ion, reporting different types of chromosomal aberrations and suggesting that Cu interacts with the formation of the spindle, distorting normal karyology. High Cr concentrations can result in eating disorders, habitat changes, enzymatic activity inhibition, histopathological changes, reduced body resistance to pathogens and mortality [63].…”
Section: Effect Of Metals/potentially Toxic Elements On Crustacean Healthmentioning
confidence: 99%